Dynamical System and Stochastic Analysis (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Almost all real-world systems are inevitably subject to random structures, parameters, and noises, and stochastic systems have been playing increasingly important roles in all areas of science and engineering.The purpose of this Special Issue is to solicit the recent achievements of control theory and applications of stochastic systems so as to further improve and develop the theoretical methods of stochastic system estimation, fault diagnosis, prognostics, and optimization, among others.